A Developmental Study on Video Games in Helping to Educate and Improve Learning Capabilities of Students in Mathematics - Soliman, Gabriel Angelo C. (Animo Repository, 2023)
Analyzing the positive impact of mathematical video games is a multifaceted process that extends beyond mere observation of students' gameplay. This research delved into a comprehensive exploration of requirements, objectives, target audience, and specific considerations pertaining to mathematics education. Employing a three-phase methodology, the study aimed to develop an interactive educational video game specifically tailored for mathematics learning. During Phase 1, an extensive analysis of existing educational games and relevant literature was conducted to identify the key factors necessary for designing effective and engaging educational video games. Drawing insights from Phase 1, Phase 2 focused on designing the video game module, incorporating feedback from experts in video game development and mathematics education. The design process encompassed careful consideration of game mechanics, instructional approaches, and design elements that align with effective mathematics learning. Phase 3 involved rigorous testing and evaluation of the video game module by experts and playtesters. Their invaluable feedback and insights contributed to iterative refinements of the game mechanics, design, and instructional approach. Challenges identified during testing were addressed to enhance the game's effectiveness in facilitating mathematics education. This developmental study provides valuable insights into harnessing the potential of video games for mathematics education, with particular emphasis on students' motivation, engagement, and persistence. The findings contribute to a deeper understanding of how video games can augment learning capabilities in mathematics. The outcomes have noteworthy implications for the development and implementation of educational video games, fostering positive learning experiences and promoting students' proficiency in mathematics.